A Statistical Analysis of Interaction Problems in Close-Proximity Multi-Seam Mines - Wai Wu; C. Haycocks (Society for Mining, Metallurgy & Exploration, 1986)
The majority of Appalachian coal deposits lie in a multi-seam environment. Historically, the decision to extract a particular seam has been based on ease of access, ownership and economics rather than ground control considerations. As mining progresses and seams are being mined out, it is increasingly common to find working and abandoned mines in close vertical proximity to each other. Such contiguous operations can produce both positive and negative ground control situations in neighboring seams. These ground control problems, defined as interaction problems, are frequently reported, and their severity can range from minor roof problems that may require no additional support to complete loss of a large section of coal reserves (Stemple, 1955; Peng & Chandra, 1980; Haycocks & Karmis, 1983; Su et al, 1984). As a consequence, interaction problems are of growing concern to the Appalachian underground coal industry. Although interaction problems in multi-seam mining have been recognized for many years and many investigations have been conducted to study the problems, the ground control principles involved in their development are only partially understood. Previous research has identified four interaction mechanisms: pillar load transfer, innerburden shearing, arching effects and upper seam subsidence (Haycocks et al, 1982; Haycocks & Karmis, 1983). Pillar load transfer mechanisms and innerburden shearing have been successfuly used to explain interaction phenomena associated with undermining operations, while arching and subsidence have been used to assess problems during overmining. In addition, interaction-controlling factors such as cover, innerburden and seam thicknesses, extraction percentages on both seams, time delay between operations on two seams, and characteristics of innerburden rock have been identified and utilized in evaluation of interaction effects (Haycocks & Karmis, 1983; Webster et a1.,1984). As an example, Figure 1 shows the relation of innerburden layering and thickness to interaction on the lower seam. The combination of such theoretical work and the analysis of case study information has made it possible to determine, with a certain degree of confidence, the interaction damage in undermining conditions. The results of such an approach have been sufficiently successful and complete to be incorporated into a software package to assist field engineers in estimating potential interaction effects when undermining a previously mined upper seam (Grenoble et al, 1984; Grenoble & Haycocks, 1985; Grenoble et al, 1985). Although the conventional finite element and photoelastic modeling techniques have been